2023
DOI: 10.1038/s41420-023-01383-4
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation enhances RSL3-induced ferroptosis to treat naïve and prevent castration-resistant prostate cancer

Abstract: Prostate cancer (PCa) is a leading cause of death in the male population commonly treated with androgen deprivation therapy that often relapses as androgen-independent and aggressive castration-resistant prostate cancer (CRPC). Ferroptosis is a recently described form of cell death that requires abundant cytosolic labile iron to promote membrane lipid peroxidation and which can be induced by agents that inhibit the glutathione peroxidase-4 activity such as RSL3. Exploiting in vitro and in vivo human and murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…After the tumor volume increased to 50–100 mm 3 , the mice were divided into the RSL3-treated group and the control group. RSL3 (20 mg/kg) or vehicle was administered intraperitoneally into mice once every two days [ 35 , 36 ]. It was shown that tumor volume and weight were markedly smaller in RSL3-treated mice than control mice, while the body weight did not differ significantly between the RSL3-treated group and control group, indicating the safety of RSL3 administration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After the tumor volume increased to 50–100 mm 3 , the mice were divided into the RSL3-treated group and the control group. RSL3 (20 mg/kg) or vehicle was administered intraperitoneally into mice once every two days [ 35 , 36 ]. It was shown that tumor volume and weight were markedly smaller in RSL3-treated mice than control mice, while the body weight did not differ significantly between the RSL3-treated group and control group, indicating the safety of RSL3 administration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, local iron overload caused ferroptosis in the decidual stromal cells by downregulating GSH and GPX4 levels [40]. An exogenous supplement of iron increased the sensitivity of cells to ferroptosis inducers [41] and enhanced RSL3-induced ferroptosis [42] in vitro. Future studies should evaluate if iron-supplementation in pregnancy may impact ferroptosis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis has been implicated in several human diseases, including PCa ( 4 ). Increasing evidence indicates that ferroptosis inhibits tumor growth ( 5 ) and the employment of ferroptosis inducers or targeting ferroptosis-related genes may represent promising strategies for treating castration-resistant PCa (CRPC) ( 6 ). Traditional Chinese medicine has multiple targets and can regulate various signaling pathways, including ADAMTS18( 7 ), reactive oxygen species (ROS) ( 8 ), nuclear factor erythroid 2-related factor 2 (Nrf2) ( 9 ) and glutathione peroxidase 4 (GPX4) ( 10 ), thereby modulating ferroptosis.…”
Section: Introductionmentioning
confidence: 99%